Democracy support and peaceful democratisation after civil war - Karina Mross (Deutsches Institut für Entwicklungspolitik (DIE), 2019)
Evidence exists that democracies are particularly stable, yet also that processes of democratisation are highly susceptible to conflict, especially if democratisation occurs in the aftermath of violent conflict. New research from the German Development Institute / Deutsches Institut für Entwicklungspolitik (DIE) indicates that external democracy support can help mitigate the destabilising effects of post-conflict democratisation. Since the 1990s, democracy support has been integral to most peacebuilding efforts. Supporting free and fair elections or a vibrant media seems well-suited for fostering peace: Democratic institutions can actively deal with societal conflicts, in sharp contrast to authoritarian regimes, which often rely on repression. However, altering power relations through more political competition can also trigger power struggles, which newly emerging democratic institutions may have difficulty containing. Therefore, questions arise regarding countries that have embarked on a process of democratisation after civil war: Can democracy support help to mitigate destabilising effects, or does it reinforce them? If it can foster peace, how should it be designed in order to avoid renewed violence? The wisdom or folly of supporting democracy to build peace after civil war has caused controversy, yet has rarely been tested empirically. This briefing paper summarises findings from DIE research that addresses this gap. The results demonstrate that: * External democracy support that accompanies postconflict democratisation can help to foster peace after civil war. Importantly, it does not trigger renewed violence. * Analysing the effects of two donor strategies to deal with trade-offs between stability (preventing renewed violence) and democracy shows that prioritising stability over democracy does not contain fewer risks than gradualist support, in contrast to widespread assumptions. In fact, the prioritising strategy can also fail, and even be counterproductive. * The competitive elements of a democratic system explain both why it can help to avoid, or provoke, renewed violence. Democracy support facilitating "controlled competition" can mitigate the destabilizing effects: Support for political competition strengthens the peaceenhancing effects by promoting meaningful choice and enabling the peaceful allocation and withdrawal of political power. Fostering institutional constraints limits the discretionary power of the executive and enforces a commitment to democratic rules. These results can provide guidance to policy-makers when engaging in post-conflict situations: 1. Donors should actively accompany post-conflict democratisation processes with substantial democracy support. They should not refrain from offering such support until stability has already proven to be sustainable, since it can make an important contribution towards strengthening peace and help in avoiding destabilising effects. 2. When facing trade-offs between stability and democracy in post-conflict situations, donors should bear in mind that prioritising stability is not less risk-prone than a gradualist approach, which promotes both stability and democracy in an iterative way. Thus, prioritising stability should not be the obvious choice in post-conflict situations. Instead, donors should carefully scrutinise the political dynamics before applying either strategy and recall that a gradualist approach offers considerable potential for strengthening peace sustainably. 3. Engaging in a context of post-conflict democratisation, donors should provide substantial support both for political competition and for institutional constraints.
Keywords: 330; Governance; Sicherheit; Frieden und fragile Staaten